Out-of-School-Time Academic Programs to Improve School Achievement: A Community Guide Health Equity Systematic Review. (November 2015) - Knopf, John A.; Hahn, Robert A.; Proia, Krista K.; Truman, Benedict I.; Johnson, Robert L.; Muntaner, Carles; Fielding, Jonathan E.; Jones, Camara Phyllis; Fullilove, Mindy T.; Hunt, Pete C.; Qu, Shuli; Chattopadhyay, Sajal K.; et al.
Abstract : Context: Low-income and minority status in the United States are associated with poor educational outcomes, which, in turn, reduce the long-term health benefits of education. Objective: This systematic review assessed the extent to which out-of-school-time academic (OSTA) programs for at-risk students, most of whom are from low-income and racial/ethnic minority families, can improve academic achievement. Because most OSTA programs serve low-income and ethnic/racial minority students, programs may improve health equity. Design: Methods of the Guide to Community Preventive Services were used. An existing systematic review assessing the effects of OSTA programs on academic outcomes (Lauer et al 2006; search period 1985-2003) was supplemented with a Community Guide update (search period 2003-2011). Main Outcome Measure: Standardized mean difference. Results: Thirty-two studies from the existing review and 25 studies from the update were combined and stratified by program focus (ie, reading-focused, math-focused, general academic programs, and programs with minimal academic focus). Focused programs were more effective than general or minimal academic programs. Reading-focused programs were effective only for students in grades K-3. There was insufficient evidence to determine effectiveness on behavioral outcomes and longer-term academic outcomes. Conclusions: OSTA programs, particularly focused programs, are effective in increasing academic achievement for at-risk students. Ongoing school and social environments that support learning and development may be essential to ensure the longer-term benefits of OSTA programs. Abstract : Supplemental Digital Content is Available in the Text.This review assesses the extent to which out-of-school-time academic programs for at-risk students from low-income and racial/ethnic minority families can improve academic achievement and in turn improve health equity.